Preparation method and application of ruthenium disulfide-copper pentasulfide positive electrode material

By adopting the nanotube structure of the cathode material of ruthenium disulfide-nine-copper pentasulfide (Cu9S5-RuS2), the problem of lack of positive electrode materials and compatibility of magnesium ion batteries is solved, and the rapid embedding and removal of magnesium ions is achieved, which significantly improves the electrochemical performance and cycling stability of the battery.

CN119706980AActive Publication Date: 2025-03-28HENAN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411837664.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Magnesium ion batteries currently face challenges such as lack of positive electrode materials, compatibility problems between electrolyte and positive electrode materials, high deposition overpotential and low charge and discharge efficiency, resulting in limited performance.

Method used

Ruthenium disulfide-Nine-copper pentasulfide (Cu9S5-RuS2) positive electrode material is used, which has a nanotube structure. By reacting copper dichloride dihydrate with thiourea and ruthenium trichloride at 160~200 °C for 4 to 10 hours, a nanotube structure with regular morphology is prepared to promote the rapid embedding and detachment of magnesium ions.

Benefits of technology

The magnesium ion battery assembled with this material has a discharge specific capacity of 118.8mAh/g after 300 cycles, and the capacity retention rate is 42.2%, which significantly improves the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium ion battery materials, and particularly relates to a preparation method of a ruthenium disulfide-copper pentasulfide (Cu9S5-RuS2) magnesium ion battery positive electrode material. According to the method, Cu9S5-RuS2 is successfully synthesized by adopting a simple hydrothermal synthesis technology and taking cupric chloride dihydrate, thiourea and ruthenium trichloride as raw materials. The Cu9S5-RuS2 prepared by the method is used as a positive electrode material of a magnesium ion battery, and shows excellent electrochemical performance. In addition, the preparation process is simple and convenient to operate, and is beneficial to promoting the technical development and commercialization process of the magnesium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium ion battery materials, and specifically relates to a preparation method of a ruthenium disulfide-copper pentasulfide electrode material and an application of the ruthenium disulfide-copper pentasulfide electrode material as a positive electrode material for a magnesium ion battery. Background Art

[0002] The global energy crisis is intensifying. The depletion of fossil fuels and price fluctuations have led to unstable energy supply. At the same time, climate change has driven the demand for clean energy. The world is facing the urgent challenge of transitioning from traditional energy to renewable energy. Although lithium batteries are widely used, they also have disadvantages such as safety issues, high cost, limited resources and environmental impact.

[0003] In contrast, magnesium-ion batteries have shown great potential in the field of energy storage due to their unique advantages. Magnesium resources are abundant and low in cost, and the divalent nature of magnesium ions gives them a theoretically higher volumetric capacity than lithium batteries. In terms of safety, magnesium-ion batteries are not prone to forming dendrites, reducing the risk of short circuits and thermal runaway. In terms of environmental protection, magnesium materials are non-toxic and easy to recycle, reducing environmental pollution. In addition, the long cycle life and stability of magnesium-ion batteries over a wide temperature range make them suitable for a variety of environments and application scenarios.

[0004] Despite this, magnesium-ion batteries still face many challenges, including a lack of cathode materials, compatibility issues between electrolyte and cathode materials, high deposition overpotential, and low charge and discharge efficiency. The slow diffusion of magnesium ions in the material limits the battery's charge and discharge performance. Currently, magnesium-ion battery technology is still in the development stage and further research is needed to improve its performance and reliability.

[0005] At present, the research on magnesium-ion batteries mainly focuses on three aspects: positive electrode materials, electrolytes, and negative electrode materials. Optimizing positive electrode materials can enhance the diffusion rate and charge storage capacity of magnesium ions, reduce overpotential, and improve battery efficiency. Sulfide positive electrode materials are conducive to the diffusion and migration of magnesium ions due to their high electrochemical activity and low charge density. The "soft" anion lattice of sulfide can weaken the Coulomb attraction between the crystal structure and magnesium ions, thereby promoting the accelerated diffusion and reversible embedding of magnesium ions. These characteristics enable sulfide positive electrode materials to exhibit fast charge and discharge capabilities and good electrochemical performance in magnesium-ion batteries.

[0006] Based on this, this application was developed. Summary of the invention

[0007] The purpose of the present invention is to provide a ruthenium disulfide-copper pentasulfide (Cu9S5-RuS2) positive electrode material in view of the defects and shortcomings of the current magnesium ion batteries. The material has a regular morphology and exhibits a nanotube structure, which is conducive to the rapid insertion and extraction of magnesium ions. The magnesium ion battery assembled using the material exhibits excellent electrochemical performance. At a current density of 100 mA / g, the battery still has a discharge specific capacity of 118.8 mAh / g after 300 cycles, and the capacity retention rate is 42.2%.

[0008] The present invention also provides a method for preparing the above-mentioned ruthenium disulfide-copper nonasulfide (Cu9S5-RuS2) positive electrode material, which is simple and economical to prepare and can significantly improve the performance of the battery.

[0009] The present invention also provides the use of the above-mentioned ruthenium disulfide-copper nonasulfide (Cu9S5-RuS2) positive electrode material as a positive electrode material for a magnesium ion battery.

[0010] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a ruthenium disulfide-copper pentasulfide positive electrode material comprises the following steps: Dissolve cupric chloride dihydrate, thiourea and ruthenium trichloride in water, and then react at a temperature of 160-200°C for 4-10 hours. After the reaction is completed, separate the solid and liquid, wash and dry to obtain the product.

[0011] Specifically, the mass ratio of the cupric chloride dihydrate, thiourea and ruthenium trichloride can be 1:0.2~0.3:0.1~0.2.

[0012] As a preferred method, the preparation method of the above-mentioned ruthenium disulfide-copper pentasulfide positive electrode material comprises the following steps: (1) Raw material preparation: Dissolve copper dichloride dihydrate and thiourea in water respectively (the solution required for the reaction can be formed by stirring for 2 to 4 hours to ensure complete dissolution and uniform mixing), obtain copper dichloride dihydrate solution and thiourea solution, mix the two, and then mix with ruthenium trichloride solution; (2) Solution transfer and high temperature reaction: The above liquid is transferred to a stainless steel reactor, placed in a muffle furnace, heated to 160-200 °C and maintained at this temperature for 4-10 h; (3) Cooling and separation: After the reaction is completed, the reactor is naturally cooled to room temperature, and the solid product is separated by filtration; (4) Washing and drying: Wash the solid product with deionized water and anhydrous ethanol respectively to remove impurities, and finally dry it.

[0013] Specifically, the concentration of the cupric chloride dihydrate solution in step (1) may preferably be 0.071 to 0.094 mol / L. The concentration of the thiourea solution may preferably be 0.040 to 0.049 mol / L. The concentration of the ruthenium chloride solution may preferably be 0.011 to 0.023 mol / L. In step (2), the liquid occupies no more than 80% of the capacity of the stainless steel reactor.

[0014] Furthermore, in step (4), the product may be first washed with deionized water for 3 to 5 times, and then washed with anhydrous ethanol for 3 to 5 times; the drying process is performed in a vacuum drying oven at a drying temperature of 45 to 80°C for a drying time of not less than 12 h.

[0015] The invention provides a ruthenium disulfide-copper pentasulfide positive electrode material prepared by the method.

[0016] The present invention provides the use of the above-mentioned ruthenium disulfide-copper pentasulfide positive electrode material as a positive electrode material for a magnesium ion battery in preparing a magnesium ion battery.

[0017] The present invention also provides a magnesium ion battery, which comprises the above-mentioned ruthenium disulfide-copper pentasulfide positive electrode material.

[0018] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects: 1. The present invention provides a simple and cost-effective method for preparing ruthenium disulfide-copper pentasulfide (Cu9S5-RuS2) cathode material.

[0019] 2. The ruthenium disulfide-copper pentasulfide (Cu9S5-RuS2) prepared by the method of the present invention has a regular morphology and exhibits a nanotube structure, which is conducive to the rapid insertion and extraction of magnesium ions.

[0020] 3. The test results show that the magnesium ion battery assembled using the ruthenium disulfide-copper pentasulfide (Cu9S5-RuS2) positive electrode material prepared by the present invention exhibits excellent electrochemical performance. At a current density of 100 mA / g, the battery still has a discharge capacity of 118.8 mAh / g after 300 cycles, and the capacity retention rate is 42.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope (SEM) image of ruthenium disulfide-copper pentasulfide prepared in Example 1; Figure 2 This is the elemental analysis (EDS) diagram of ruthenium disulfide-copper pentasulfide prepared in Example 1; Figure 3A cyclic voltammetry curve of a magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide prepared in Example 1 as the positive electrode material at a scan rate of 1.0 mV / s; Figure 4 A charge and discharge curve diagram of a magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide prepared in Example 1 as the positive electrode material at different current densities; Figure 5 A charge-discharge curve diagram of a magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide prepared in Example 1 as the positive electrode material at different cycle times at a current density of 50 mA / g; Figure 6 This is a cycle stability curve of a magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide prepared in Example 1 as the positive electrode material at a current density of 100 mA / g. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the embodiments described below.

[0023] Through these embodiments, we hope to more comprehensively demonstrate the technical details and application effects of the present invention, but the actual application scope of the present invention may be broader and not limited to the following description.

[0024] In the following examples, unless otherwise specified, the raw materials used are common commercial products that can be directly purchased or can be prepared using conventional techniques in the art.

[0025] Room temperature refers to 25±5℃.

[0026] Example 1 A method for preparing a ruthenium disulfide-copper pentasulfide positive electrode material, the specific implementation steps of which are as follows: 0.2 gCuCl2·2H2O was dissolved in 15 mL water (stirred for 3 h to promote complete dissolution), 0.0468 g thiourea was dissolved in 15 mL water (stirred for 3 h to promote complete dissolution), and then the two solutions of cupric chloride dihydrate and thiourea were mixed together, and ultrasonic treatment was used to ensure uniform mixing, and then stirred for 3 h to promote dissolution, and mixed solution A was obtained. 0.0239 g RuCl3 was dissolved in 10 mL water to obtain mixed solution B, and then mixed solution A and mixed solution B were mixed and transferred to a stainless steel reactor, and the reactor was placed in a muffle furnace, heated to 180 ° C and maintained for 6 h. After the reaction was completed, it was cooled to room temperature, filtered, and the solid product was separated, and washed with deionized water and anhydrous ethanol 4 times each. The washed product was dried in a vacuum drying oven at 60 ° C for 24 h to obtain ruthenium disulfide-copper pentasulfide positive electrode material (Cu9S5-RuS2).

[0027] Figure 1 The scanning electron microscope (SEM) image of ruthenium disulfide-copper pentasulfide prepared in Example 1 is given. Figure 1 As shown, the microscopic morphology of ruthenium disulfide-copper pentasulfide (Cu9S5-RuS2) prepared in this embodiment presents a nanotube structure, and these nanotubes are aggregated from multiple nanospheres.

[0028] Figure 2 The elemental analysis (EDS) diagram of ruthenium disulfide-copper pentasulfide prepared in Example 1 is given. Figure 2 As shown, the energy spectrum of ruthenium disulfide-copper pentasulfide (Cu9S5-RuS2) prepared in this embodiment shows that the material is mainly composed of Cu, Ru and S elements.

[0029] Example 2 The ruthenium disulfide-copper pentasulfide positive electrode material prepared in Example 1 is applied to a magnesium ion battery, and the steps are as follows: Preparation of the positive electrode: The Cu9S5-RuS2 electrode sheet is mainly prepared by mixing Cu9S5-RuS2, conductive carbon black, and polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1, specifically: 0.01 g of PVDF is added to 1.5 mL of NMP (N-methylpyrrolidone) and mixed evenly to obtain a PVDF-NMP solution. Conductive carbon black and Cu9S5-RuS2 prepared in Example 1 are added to the PVDF-NMP solution in sequence and stirred for 6 h. The stirred slurry is coated on a carbon cloth current collector with a diameter of 12 mm, first dried in a 60 ° C blast oven for 30 min, then transferred to a vacuum drying oven, and dried at 120 ° C for 6 h.

[0030] Assembly: The battery was assembled using a CR2032 button battery shell. A commercial magnesium sheet with a thickness of 2.5 mm and a diameter of 14 mm was used as the negative electrode, a glass fiber membrane with a diameter of 16 mm was used as the separator, a carbon cloth current collector loaded with Cu9S5-RuS2 with a diameter of 12 mm prepared in Example 1 was used as the positive electrode sheet, and Mg(TFSI)2-AlCl3-MgCl2-DME was used as the electrolyte (for the specific electrolyte formula, please refer to the literature Xiaolan Xue, et. al., Boosting the cycling stability of rechargeable magnesium batteries by regulating the compatibility between nanostructural metal sulfide cathodes and non-nucleophilic electrolytes, DOI:10.1007 / s12274-022-4932-z, Volume 16, pages 2399–2408, (2023)). The negative electrode shell, spring sheet, gasket, magnesium sheet, electrolyte, diaphragm, electrolyte, positive electrode sheet, gasket and positive electrode shell are assembled in the order of negative electrode shell, and the assembly process is carried out in a glove box filled with argon (H2O and O2<0.01 ppm).

[0031] Cyclic voltammetry test: An electrochemical workstation (CHI 660E, Shanghai Chenhua) was used to study the peak position of the battery's oxidation / reduction reaction during the cycle. The test voltage range was 0-2.5 V, and the scan rate was 1 mV s −1 .

[0032] Rate performance test: Wuhan LAND CT3002A battery testing system was used to carry out charge and discharge tests at current densities of 50 mA / g, 100 mA / g, 200 mA / g, and 500 mA / g.

[0033] Cycle performance test: Wuhan LAND CT3002A battery testing system was used to test the constant current charge and discharge performance of the button battery at a current density of 50 mA / g; the cycle stability performance of the button battery was tested at a current density of 100 mA / g, and the number of cycles was set to 300.

[0034] Figure 3 The cyclic voltammetry curve of the magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide as the positive electrode material prepared in Example 1 at a scan rate of 1.0 mV / s is given. Figure 3As shown, the assembled battery was subjected to cyclic voltammetry testing, and it can be clearly seen that: the Mg deposition / dissolution process is highly reversible, and as the number of cycles increases, the redox peak position does not shift significantly, and the CV curves almost overlap, showing good reversibility of the Mg storage reaction.

[0035] Figure 4 The charge and discharge curves of the magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide as the positive electrode material prepared in Example 1 at different current densities are given. Figure 4 As shown, the assembled battery is tested at different rates. By observing the charge and discharge curves at different current densities, the discharge and charge platforms can be clearly seen, which indicates that the battery has excellent structural stability.

[0036] Figure 5 The charge and discharge curves of the magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide as the positive electrode material prepared in Example 1 at different cycle times at a current density of 50 mA / g are given. Figure 5 As shown, at a current density of 50 mA / g, the charge and discharge platform of the assembled battery does not change much with the increase in the number of cycles, showing good stability, and the specific capacity of the battery is always maintained above 200 mAh / g, which indicates that the battery has a high energy storage capacity.

[0037] Figure 6 The cycle stability curve of the magnesium ion battery assembled with ruthenium disulfide-copper pentasulfide as the positive electrode material prepared in Example 1 at a current density of 100 mA / g is given. Figure 6 As shown, at a current density of 100 mA / g, the assembled battery still has a discharge capacity of 118.8 mAh / g after 300 cycles, and the capacity retention rate is 42.2%.

[0038] In summary, the preparation method of the ruthenium sulfide-copper pentasulfide (Cu9S5-RuS2) positive electrode material of the present invention is not only simple and economical, but also can effectively improve the battery performance, including the stability and cycle life at different current densities, which is of great significance for the development and application of battery technology.

[0039] The above-mentioned embodiments are only preferred embodiments of the present invention, but this does not mean that these embodiments limit the scope of protection of the invention. Any non-substantial changes, improvements or substitutions made on the basis of the present invention, as long as these changes do not exceed the core concept and technical solution of the invention, are within the scope of protection required by the invention.

Claims

1. A method for preparing a ruthenium disulfide-copper pentasulfide positive electrode material, characterized in that: Dissolve cupric chloride dihydrate, thiourea and ruthenium trichloride in water, and then react at a temperature of 160-200 °C for 4-10 hours. After the reaction is completed, separate the solid and liquid, wash and dry to obtain the product.

2. The method for preparing the ruthenium disulfide-copper pentasulfide positive electrode material according to claim 1, characterized in that: The mass ratio of the cupric chloride dihydrate, thiourea and ruthenium trichloride is 1:0.2-0.3:0.1-0.

2.

3. The method for preparing the ruthenium disulfide-copper pentasulfide positive electrode material according to claim 1, characterized in that: The following steps are involved: Preparation of raw materials: Dissolve copper dichloride dihydrate and thiourea in water respectively to obtain copper dichloride dihydrate solution and thiourea solution, mix the two, and then mix with ruthenium trichloride solution; Solution transfer and high temperature reaction: transfer the above liquid to a stainless steel reactor, place it in a muffle furnace, heat it to 160-200 °C and maintain this temperature for 4-10 h; Cooling and separation: After the reaction is completed, the reactor is naturally cooled to room temperature and the solid product is separated by suction filtration; Washing and drying: Wash the solid product with deionized water and anhydrous ethanol respectively, and finally dry it.

4. The method for preparing the ruthenium disulfide-copper pentasulfide positive electrode material according to claim 3, characterized in that: The concentration of the cupric chloride dihydrate solution in step (1) is 0.071-0.094 mol / L.

5. The method for preparing the ruthenium disulfide-copper pentasulfide positive electrode material according to claim 1, characterized in that: The concentration of the thiourea solution in step (1) is 0.040-0.049 mol / L.

6. The method for preparing the ruthenium disulfide-copper pentasulfide positive electrode material according to claim 1, characterized in that: The concentration of the ruthenium trichloride solution in step (1) is 0.011-0.023 mol / L.

7. The method for preparing the ruthenium disulfide-copper pentasulfide positive electrode material according to claim 1, characterized in that: In the step (4), the sample is first washed with deionized water for 3 to 5 times, and then washed with anhydrous ethanol for 3 to 5 times; the drying process is carried out in a vacuum drying oven at a drying temperature of 45 to 80°C for a drying time of not less than 12 hours.

8. Ruthenium disulfide-copper pentasulfide positive electrode material prepared by the method according to any one of claims 1 to 7.

9. Use of the ruthenium disulfide-copper pentasulfide positive electrode material according to claim 8 as a positive electrode material for a magnesium ion battery in the preparation of a magnesium ion battery.

10. A magnesium ion battery, characterized in that: Contains the ruthenium disulfide-copper pentasulfide positive electrode material as described in claim 8.

Citation Information

Patent Citations

  • Ruthenium oxide-copper sulfide composite material, application thereof and electrode plate for supercapacitor

    CN106024408A

  • Sulfur / sulfide / copper ternary composite cathode and preparation and application thereof in magnesium-sulfur battery

    CN106935796A

  • Copper pentasulfide / ferric oxide composite electrode material and preparation method thereof

    CN113764196A